2009
DOI: 10.1242/jeb.028449
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of PHA-induced immune response and plasma carotenoids in birds:should we have a closer look?

Abstract: SUMMARYAllocation trade-offs of limited resources are thought to ensure the honesty of sexual signals and are often studied using controlled immune challenges. One such trade-off between immunity and ornaments is that involving carotenoids. Phytohemagglutinin (PHA)-induced immune response is a widely used immune challenge, yet more details on the underlying physiological mechanisms and potential costs are needed. We investigated the temporal dynamics of PHA-induced immune response and associated changes in blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
50
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 52 publications
3
50
2
Order By: Relevance
“…Carotenoids are known to regulate and stimulate immune function (Hõrak et al, 2004;Biard et al, 2009;Cote et al, 2010;Hill and Johnson, 2012) and to participate in reducing oxidative stress (Surai and Speake, 1998;Blount et al, 2000;Isaksson, 2009). We experimentally investigated the influence of dietary carotenoids on oxidative stress in the great tit after moult, by simultaneously manipulating carotenoid availability and physical activity, the latter being an attempt to increase oxidative stress as a result of an increase in metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Carotenoids are known to regulate and stimulate immune function (Hõrak et al, 2004;Biard et al, 2009;Cote et al, 2010;Hill and Johnson, 2012) and to participate in reducing oxidative stress (Surai and Speake, 1998;Blount et al, 2000;Isaksson, 2009). We experimentally investigated the influence of dietary carotenoids on oxidative stress in the great tit after moult, by simultaneously manipulating carotenoid availability and physical activity, the latter being an attempt to increase oxidative stress as a result of an increase in metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…oxidative damage) in egg yolk (Surai and Speake, 1998;Blount et al, 2002) and in passerine adults and nestlings plasma carotenoid concentrations were positively correlated with plasma vitamin A and E concentrations (Biard et al, 2005(Biard et al, , 2007, which are important lipid-soluble antioxidants (Surai, 1999(Surai, , 2002. After an immune stimulation, plasma carotenoid concentration decreased in blackbirds Turdus merula (Biard et al, 2009) and in zebra finches Taeniopygia guttata (Alonso-Alvarez et al, 2004). Moreover, plasma carotenoid concentration was positively correlated with concentrations of lymphocytes and eosinophils in the great tit (Hõrak et al, 2004).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…A recent meta-analysis concluded that carotenoid levels in birds are related to individual immune response and antioxidant capacity (Simons et al, 2012). For example, the inflammatory/immune response elicited by the injection of a vegetal protein (PHA test) is associated to a decrease in the levels of carotenoids in blood (Biard et al, 2009). However, it is unclear if carotenoids act properly as antioxidants or just are affected by organisms antioxidant status (Simons et al, 2012).…”
mentioning
confidence: 99%
“…The PHA injection stimulate an inflammatory response, the influx of lymphocytes, neutrophils, basophils, eosinophils and macrophages to the local of the injury (Martin et al 2003;Kennedy and Nager, 2006;Tella et al, 2008;Biard et al, 2009;Vinkler et al, 2010;.…”
Section: Discussionmentioning
confidence: 99%